15 lies women are told at work : ... and the truth we need to succeed - Hammer, Bonnie (Simon Element, 2024)
"Bonnie Hammer's legendary career spans five decades in a turbulent, male-driven industry. Today, Bonnie is a powerful leader at the very top of her field, and women at all levels constantly ask her: What is your secret to success? Her power--and her staying power--comes from rejecting common myths about how women are "supposed" to act in the workplace. She knows that the conventional wisdom women are told about work--pithy phrases like "Don't mix work with play," "Talk is cheap," "Follow your dreams," "Know your worth," "Trust your gut," and "You can have it all,"--hold women back. Having risen from an entry-level production assistant whose chief charge was a dog to a transformative top executive at NBCUniversal, Bonnie challenges workplace misperceptions and shares the uncommon sense women need to succeed"--